ANALISIS ATAS REVIU LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN MINAHASA - Manampiring, Ryane B.T.; Tinangon, Jantje J.; Affandi, Dhullo (Universitas Sam Ratulangi, 2017)
Regional autonomy is an effort of regional empowerment in making regional decisions more freely and is responsible for managing the resources owned. The Regional Head has an obligation to account for the use of local budgets to the DPRD and the general public. The accountability report is a Financial Report prepared by the Regional Government. Before the report is given to the regional head of LKPD, it should be reviewed by the inspectorate to obtain sufficient confidence whether the financial statements have been prepared in accordance with government accounting standards and have been presented in accordance with the appropriate internal control system. The reviews consist of planning, and reporting. Based on the results of this study, the implementation of review of LKPD by Inspectorate of Fiscal Year 2015 and 2016 in Minahasa District has not been in accordance with the Implementation Guidelines of the Revision as stipulated in the Regulation of the Minister of Home Affairs Number 4 Year 2008 on Guidance of Implementation of LKPD Review. This is due to the absence of adequate review planning in the SPI assessment, and the implementation of reviews that are not in accordance with the schedule.Keyword :Â Review Inspektorat, Government Financial Report (LKPD)